1996
DOI: 10.1073/pnas.93.22.12359
|View full text |Cite
|
Sign up to set email alerts
|

Absence of fetal liver hematopoiesis in mice deficient in transcriptional coactivator core binding factor beta.

Abstract: Core binding factor 13 (CBF,B) is considered to be a transcriptional coactivator that dimerizes with transcription factors core binding factor a 1 (CBFA1), -2, and -3, and enhances DNA binding capacity of these transcription factors. CBFI3 and CBFA2, which is also called acute myeloid leukemia 1 gene, are frequently involved in chromosomal translocations in human leukemia. To elucidate the function of CBFP, mice carrying a mutation in the Cbfb locus were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
230
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(240 citation statements)
references
References 35 publications
(42 reference statements)
8
230
1
1
Order By: Relevance
“…The consensus DNA sequence recognized by AML1, TGT/cGGT (Meyers et al, 1993), is contained in the promoter and enhancer regions of many hematopoietic-speci®c genes . Although murine genes encoding AML2 and AML3 have been identi®ed (Levanon et al, 1994), an essential role for AML1 in hematopoiesis was demonstrated by AML1 (Okuda et al, 1996;Wang et al, 1996a) and CBFb (Niki et al, 1997;Sasaki et al, 1996;Wang et al, 1996b) knock-out experiments. Mice that lack AML1 or CBFb have absent fetal liver hematopoiesis and die between days E11.5-13.5 with a distinct pattern of central nervous system hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…The consensus DNA sequence recognized by AML1, TGT/cGGT (Meyers et al, 1993), is contained in the promoter and enhancer regions of many hematopoietic-speci®c genes . Although murine genes encoding AML2 and AML3 have been identi®ed (Levanon et al, 1994), an essential role for AML1 in hematopoiesis was demonstrated by AML1 (Okuda et al, 1996;Wang et al, 1996a) and CBFb (Niki et al, 1997;Sasaki et al, 1996;Wang et al, 1996b) knock-out experiments. Mice that lack AML1 or CBFb have absent fetal liver hematopoiesis and die between days E11.5-13.5 with a distinct pattern of central nervous system hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“…The t(8;21) translocation generates an AML1/ETO fusion protein whereas the heterodimeric partner of AML1, CBFb, is involved in the inv(16) abnormality, which generates a CBFb-MYH11 fusion product (Liu et al, 1993). AML1 (also called CBFA2) and CBFb play essential roles in hematopoietic development; homozygous disruption of either gene in mice, using targeted homologous recombination, results in absent fetal liver hematopoiesis, extensive CNS hemorrhage and death on postcoital day (dpc) 12.5 (Okuda et al, 1996;Wang et al, 1996a,b;Sasaki et al, 1996). At least three isoforms of human AML1 proteins have been identi®ed, AML1 (also called AML1A), AML1b, and AML1c (also called AML1B).…”
Section: Introductionmentioning
confidence: 99%
“…The a subunit, with DNA binding properties, contains a region of homology with the runt gene of Drosophila (Daga et al, 1992) and the b subunit stabilizes the binding of the a subunit to DNA. Recent work has demonstrated that both subunits are essential for a correct hematopoiesis (Okuda et al, 1996;Wang et al, 1996a,b;Castilla et al, 1996;Sasaki et al, 1996;Yergeau et al, 1997;Niki et al, 1997) and that their disruption may be crucial for leukemogenesis. Other genes are found involved together with the CBF genes in di erent leukemia subtypes.…”
Section: Introductionmentioning
confidence: 99%